Examination of Quality Control Parameters in some Diagnostic X-ray Units (Journal of Nuclear Technology in Applied Science, 2019)
Periodical performance of quality control in diagnostic x-ray machines is important to provide minimum dose delivered to patients and high image quality. The current study is aimed to assure the quality control of conventional X-ray machines over some Makkah city hospitals according to quality control protocol and the measured parameters values are compared to the international acceptance limits. Some factors affecting on quality assurance of conventional X-ray machines such as reproducibility of time, applied high voltage, kilo-voltage accuracy, time accuracy, linearity and half value layer of X-ray machines over four hospitals in Makkah city are investigated. These parameters are measured by using the RaySafe solid-state detector connected with suitable ionization chambers located at 100 cm source to image detector. Time Reproducibility ranged from 0.05% to 0.07% and high voltage reproducibility ranged from 0.09% to 0.14 %. Kilo-voltage accuracy ranged from 0.22 to 3.5 % and time accuracy ranged from 0.02 to 4.1% respectively. Coefficients of linearity of diagnostic X-ray units in four hospitals in KSA were 0.02, 0.004, 0.02 and 0.24. This study concluded that quality control examinations are within the tolerance limit of the American Association of Physicist in Medicine, “(AAPM)”. It assists in the optimization of a dose delivered to patients.
Keywords: Quality Control; Reproducibility; Accuracy; Linearity Diagnostic X-ray; RaySafe